Modern learners and changing trends: flipped classrooms in medical education - Shubhangi Mhaske (Al Ameen Journal of Medical Sciences)
In the ever-evolving landscape of medical education, the chase for effective training methodologies has never been more pressing. Traditional didactic methods, which often involve passive learning through lectures, are increasingly seen as inadequate in preparing future healthcare professionals for the complexities of modern medical practice. This inadequacy stems from the dynamic and multifaceted nature of healthcare, where theoretical knowledge must seamlessly integrate with practical skills and critical thinking. Against this backdrop, the flipped classroom model has emerged as a transformative approach, aligning with outcome-based competency frameworks to enhance medical training. This editorial explores the potential of the flipped classroom to meet contemporary educational needs in medical training, supported by literature references and practical insights.